2004
DOI: 10.1016/j.ejvs.2004.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Hypoplasia of the Great Saphenous Vein and Varicose Disease

Abstract: Saphenous hypoplasia occurs in varicose limbs more frequently than in healthy ones (p= >0.001). It greatly influences the path of the reflux and the anatomy of the varicose veins. GSV segmental hypoplasia can be detected preoperatively by duplex ultrasonography. Its occurrence may influence surgical management for two main reasons: in about 68% of varicose limbs with segmental hypoplasia, the distal GSV is competent. If the distal GSV is varicose, its size and flow direction is normalised by treating the acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
64
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 15 publications
3
64
0
3
Order By: Relevance
“…If there is no connection between the two segments of the GSV, then only one segment may develop incompetence. Segmental hypoplasia is present in 25% of limbs with GSV reflux due to SFJ incompetency and in 12% of limbs in normal subjects (P < 0.01) (15). Another study also showed that the incidence of a segmental hypoplasia of the GSV was higher in patients with varices than in normal subjects (43% versus 30%; statistical significance is not defined) (13).…”
Section: Hypoplasia Of the Gsvmentioning
confidence: 91%
See 4 more Smart Citations
“…If there is no connection between the two segments of the GSV, then only one segment may develop incompetence. Segmental hypoplasia is present in 25% of limbs with GSV reflux due to SFJ incompetency and in 12% of limbs in normal subjects (P < 0.01) (15). Another study also showed that the incidence of a segmental hypoplasia of the GSV was higher in patients with varices than in normal subjects (43% versus 30%; statistical significance is not defined) (13).…”
Section: Hypoplasia Of the Gsvmentioning
confidence: 91%
“…Another study also showed that the incidence of a segmental hypoplasia of the GSV was higher in patients with varices than in normal subjects (43% versus 30%; statistical significance is not defined) (13). The higher incidence of segmental GSV hypoplasia in patients with clinically apparent varicose veins may play a causative role in the pathogenesis of varices (13,15). Despite the high incidence of hypoplasia of the GSV, it has been mentioned rarely in the literature.…”
Section: Hypoplasia Of the Gsvmentioning
confidence: 94%
See 3 more Smart Citations